Model of dynamic indication in the bar graph form - Bushma, A.V.; Sypko, N.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2002)
The main principles of formation of dynamic bar graph representation using display with a matrix electric connection of elements have been considered in this work. Applying the theory of sets we formalized a synthesis of symbols and obtained logic operators describing a formation of a visual image at the display information area. Offered and analysed is the information model for the bar graph form of information representation using the scale with scanning along the columns (elder digits) of the element matrix.